IMPLEMENTING SPIRITUAL LEARNING STRATEGIES TO SHAPE STUDENTS CHARACTER IN PUBLIC ELEMENTARY SCHOOLS IN INDRAGIRI HILIR - Zulkarnainsyah, Zulkarnainsyah; Zulkifli, Zulkifli (Sekolah Tinggi Agama Islam Al Hidayah, 2025)
Purpose: This study aims to analyze the implementation of spiritual learning strategies in shaping students’ character at two public elementary schools in Indragiri Hilir Regency, namely SDN 015 Tanjung Pasir (urban context) and SDN 014 Sungai Nyiur (rural/coastal context). Method: A qualitative descriptive approach was employed, with data collected through in-depth interviews, observations, documentation, and triangulation of sources and methods. Research participants included school principals, Islamic education teachers and classroom teachers, upper-grade students (Grades IV–VI), and parents or school committee members. Result: The findings indicate that spiritual learning strategies are implemented contextually according to each school’s social and environmental characteristics. Urban schools tend to apply structured, school-based spiritual programs, while rural/coastal schools develop collaborative, community-based approaches grounded in local wisdom. Conclusion: Both models demonstrate a positive impact on students’ character formation, particularly in strengthening religiosity, discipline, responsibility, empathy, and social awareness. Implication: This study contributes theoretically by enriching the discourse on spiritual-based character education within public elementary school settings and practically by proposing adaptive models of spiritual learning aligned with the Pancasila Student Profile (P5). The findings highlight the importance of flexible, contextual, and collaborative character education strategies as an integral component of elementary education policy and practice in Indonesia.